Pengaruh Disiplin dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan PDAM Tirta Jam Gadang Kota Bukittinggi - Siska, Adilla Juita; Sumpeno, Ochi (Jurusan PIPS FKIP UMMY Solok, 2021)
This study aims to determine the effect of discipline and work motivation on employee job satisfaction at PDAM Tirta Jam Gadang in Bukittinggi City. To conduct the research, the authors used data from a structured questionnaire and a sample of 75 employees of PDAM Tirta Jam Gadang, Bukittinggi City. This study uses the SPSS version 22 program and the test instruments used are validity and reliability tests using binary logistic regression analysis. The results of the analysis show that discipline has a positive and significant effect on employee job satisfaction at PDAM Tirta Jam Gadang, Bukittinggi City and motivation has a positive and significant influence on employee job satisfaction at PDAM Tirta Jam Gadang in Bukittinggi City and the most dominant variable affecting satisfaction is Work discipline. Keywords : Job satisfaction, work discipline and work motivation